2004
DOI: 10.1143/jjap.43.l1482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound on Rate of Flow through Porous Media

Abstract: In this paper, we present the results of laboratory tests conducted to investigate ultrasonically enhanced flow rate using specially designed and fabricated equipment. The influencing factors i are verified to investigate the effect of ultrasound on a soil matrix and a flowing liquid. The conditions tested were soil type, temperature and ultrasonic energy. The test results indicate that ultrasound enhances flow rate significantly. The degree of enhancement and the values of influencing factors, i , however, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The effect of ultrasound on flow rate through soils was reported by Kim et al 1) However, available information about the effects of ultrasound on the extraction of contaminants from porous media is limited and piecemeal. Iovenitti et al 2) reported a 6 -26% improvement in surrogate contaminant extraction using ultrasound.…”
mentioning
confidence: 95%
“…The effect of ultrasound on flow rate through soils was reported by Kim et al 1) However, available information about the effects of ultrasound on the extraction of contaminants from porous media is limited and piecemeal. Iovenitti et al 2) reported a 6 -26% improvement in surrogate contaminant extraction using ultrasound.…”
mentioning
confidence: 95%